Inovasi Pelayanan Administrasi Kependudukan Go-Online (Gool) Dinas Kependudukan Dan Pencatatan Sipil Kota Probolinggo - Isharyono, Achmad Budi; Hardjati, M.AP, Dra. Susi (Institut Riset dan Pengembangan Indonesia, 2023)
Population administration is an important document to be owned by every citizen. As well as being usefulfor self-identification, population documents will later also function to access various public services. TheDepartment of Population and Civil Registration of Probolinggo City in improving the services providedto the community created a population service innovation called Go-Online (GOOL). This step is the bestsolution in facilitating the community in managing population administration. Dispendukcapil ofProbolinggo City continues to try to optimize services through online system innovation. However, withthis innovation, deficiencies and weaknesses were still found in its development, especially the culture ofthe Probolinggo people who are still adapting to this innovation. This research method is descriptivequalitative with primary data collection through in-depth interviews and observations from related informants.Based on the results of the study that: 1. Relative Advantage that people in Probolinggo Citystill tend to prefer using offline services rather than online because service innovation is also in atransitional period in changing the culture of people who were previously offline to switch to onlineservices. 2. Compatibility, the process of adjusting the Go-Online population administration serviceinnovation (GOOL) is still in a transitional state of adjustment from offline to online services, experiencingobstacles due to the culture of the people of Probolinggo City, who on average are still accustomed tousing offline services, so it takes time. in the service innovation development process. 3. Complexity of theGo-Online population administration service (GOOL) where there is learning and adjustment, due toongoing socialization with existing procedures. 4. Triability The Go-online service innovation (GOOL) ofthe Probolinggo City Population and Civil Registration Service is able to provide convenience and cuttimes faster than offline services. 5. Observeability (observable) the presence of the Go-online PublicService Innovation (GOOL) in Probolinggo City, namely the service time provided is faster and easier thanbefore the innovation.